(untitled) - Zied, Elisa (Hoboken, NJ, 2007)
With nutritional guidelines and recipes designed to make family meals simple, healthy, and delicious, this indispensable guide shows how to make a nutrition plan for each member of the family, set realistic goals, achieve and maintain a healthy weight, make fitness fun, and eat healthy at home or at restaurants.
Keywords: Nutrition,Consumer education,Dinh dưỡng,Giáo dục người tiêu dùng